Tomographic Evaluation of the Efficacy of Three Rotary Retreatment Systems for Retreatability of Root Canals Obturated with Two Different Techniques - Tareq Azeez Hamzah; Maha Mosaid Yahya Albazzaz (Engineering Proceedings)
The objective of this in vitro study was to compare the efficacy of three different rotary systems, namely D-RaCe, R-Endo, and Edgefile XR, in the removal of root canal obturation materials during non-surgical retreatment procedures. Lower first premolars with straight oval canals were utilized, and microcomputed tomography (micro-CT) was employed as an evaluation method. The study also aimed to investigate the influence of two different initial obturation methods, the single cone and the continuous wave compaction techniques, on the amount of residual material after retreatment. The findings revealed that none of the retreatment systems could completely eliminate the obturation material, corroborating existing studies. However, Edgefile XR outperformed the other systems in terms of reduced residual material. The continuous wave compaction method for initial obturation resulted in fewer remnants compared to the single cone technique. This contradicts prior research suggesting that the two methods offer comparable sealing abilities. The study underscores the advantages of using micro-CT for evaluation, as it provides a more accurate three-dimensional assessment of the residual materials in the canals. Despite its limitations, such as the focus on straight canals and the in vitro setting, the study provides crucial insights for clinicians. It suggests that the choice of rotary system and initial obturation method can significantly impact the success of root canal retreatment procedures.